Metagenomic insights into respiratory viral signatures in lower respiratory tract infections with and without respiratory failure - Zhu, Ning; Gao, Jinying; Wu, Ruihong; Jia, Shanshan; Guo, Xiaohan; Sun, Dong; Guan, Qingtian (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveLower respiratory tract infections (LRTIs) are a significant cause of morbidity and mortality worldwide, with the respiratory microbiome playing a pivotal role in disease pathogenesis. Comprehensive profiling of the lower respiratory tract virome allows investigation of potential differences between LRTIs and non-LRTIs, helps identify virus-associated taxa linked to pulmonary disease, and provides insights into virome–host interactions involved in respiratory health.MethodsIn this study, we compared viral and bacterial microbiome characteristics of LRTI patients with non-LRTI controls by α-diversity, β-diversity (PCoA, NMDS, ANOSIM), and differential abundance (LEfSe) analyses using metagenomic sequencing of bronchoalveolar lavage fluids, and further performed these comparisons similarly in respiratory failure (RF) patients and non-RF patients in the LRTI group. In addition, virus–bacteria co-occurrence patterns, the correlations between viral and bacterial abundance profiles, and the associations between microbial features and host clinical indicators were assessed using Spearman correlation analysis.ResultsOverall, no significant differences in viral and bacterial α- or β-diversity were detected between LRTI (n=39) and non-LRTI (n=9) groups. However, among LRTI patients with RF (n=5), distinct viral taxonomic signatures were observed, including enrichment of Phixviricota, Malgrandaviricetes, Petitvirales, and Microviridae lineages. Despite taxonomic shifts, overall viral diversity remained similar between RF and non-RF subgroups. Bacterial communities showed no notable stratification across clinical categories. Correlation analyses revealed that uncultured human fecal viruses were negatively associated with lymphocyte counts, while Streptococcus-related bacteriophages correlated positively with C-reactive protein (CRP) levels.ConclusionThe overall composition and diversity of the respiratory microbiome were insufficient to distinguish LRTI from non-LRTI conditions. However, within the LRTI cohort, patients with RF exhibited distinct viral taxonomic profiles compared to non-RF individuals. Additionally, several viral taxa were correlated with host clinical indicators irrespective of clinical subgroup. These findings highlight virome compositional differences associated with RF within LRTI patients, but do not imply causal effects, and warrant further investigation.